Про iснування неперервних на R+ розв’язкiв систем нелiнiйних диференцiально-функцiональних рiвнянь - Денисенко, Н.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
New sufficient conditions of the existence of solutions continuously differentiable on R+ to the system of nonlinear differential-functional equations with a linearly transformed argument have been obtained.